MAHMOUD AHMADINEJAD (STUDI PEMIKIRAN DAN DAMPAK PEMIKIRAN POLITIK TAHUN 2005-2012) - Lestari, Menik (Candi, 2013)
The aim of this research is to know the : ( 1 ) How is the development of political thought Mahmoud Ahmadinejad in the course of his political career after the Islamic revolution of Iran; ( 2 ) How does the impact posed by the political thought Ahmadinejad against economic, social and foreign politics of Iran. This research using a method of historical research, with the procedure a heuristic, criticism, interpretation, and historiografi. Based on the results of of the study can be summed up as follows. First, the political thought Mahmoud Ahmadinejad about justice, even distribution,  freedom, and democracy grows and develops from university bench influenced doctrine, ideology, and thought Khomeini. Second the impact of the radical Mahmoud Ahmadinejad's thought and vocal in the field of economic, social, and political conditions in Iran making increasingly critical because of the depressed by the embargo and the isolation of Western politics is done in various aspects of life. Key words : ideology, political thought, Iran, Mamoud Ahmadinejad.